Pengaruh Pemberian Teh Hijau terhadap Tekanan Darah dan Kadar Kolesterol (LDL) pada Lansia dengan Hipertensi - Sriyono,; Proboningsih, Jujuk (Jurusan Keperawatan FIKES UNSOED, 2012)
The purpose of this study is to explore the effect of green tea on the level of blood pressure and LDL in patient with hypertension at UPT Pelayanan Sosial Lansia Pasuruan. The design was a quasi experimental study using a equivalent control group with pre and post test approach. A total sampling of 20 patients employed as an intervention group and a control group of 20 patients. Green tea have showed a ability to reduce the level of systolic and diastolic blood pressure (p= 0,001). It is recommended to conduct further research using appropriate number of samples, composition test of green tea characteristic, and also using repeated measure approach.